Synphytoindication modelling of climatopes of forest ecosystems based on the forest monitoring data for forest-steppe region in Ukraine - Bondaruk, M. A.; Buksha, I. F.; Tselishchev, O. G. (Forestry and Forest Melioration, 2020)
Introduction The methodical approaches to synphytoindication modelling and examples of their application presented in the work, reveal the prospects of the research area for regional (zonal) ecological monitoring of climatic regimes in forest ecosystems. Materials and Methods The study involves forest vegetation on 642 first-level forest monitoring plots within Forest-Steppe forestry region in Ukraine (49 forest types in 15 types of forest site conditions are represented). The method of phytoindication of major factors on unified ecological scales for Ukrainian flora species (Didukh 2011) was used to indicate ecoregimes in forest ecosystems to define such microclimatic indicators of the ecotopes as thermoregime, ombroregime, contrast regime, cryoregime, as well as to describe how they change within different forest site conditions (Didukh 2011). Synphytoindication modelling of forest ecosystem climatops for regional (zonal) monitoring of climatic regimes of forest ecosystems was carried out by calculating background levels (average value within standard deviations) of climatic factors (thermophone, contrastophone, ombrophone, cryophone) for coniferous, mixed and deciduous forests and for all Forest-Steppe forestry region (Bondaruk 2015). Results Climatops of forests within Forest-Steppe forestry region are characterized by the following variability of microclimatic indicators (within standard deviations): thermophone is close to submesothermal (Tm = 40–45 kcal/cm2 per year, or 1,675–1,884 MJ m2/year); ombrophone is from sub-ombrophytic to intermediate between sub-ombrophytic and meso-ombrophytic (Om from 0…+200 mm to +200…+400 mm); contrastophone is intermediate between hemioceanic and hemicontinental (Kn = 121…130%); cryophone is from intermediate between subcryophytic and hemicryophytic (Cr = -10.0…-6.0 ?C) between moderate and mild winters to hemicryophytic with mild winters (Cr = -6.0…-2.0 ?C) . The trends in the dynamics of phytoindication indicators of climatic regimes depending on the changes in forest site conditions have been determined. Thus, the ecotopes of infertile pine sites and fairly infertile pine sites are characterized by the lowest average values of the thermoclimate; those of fairly fertile sites and fertile sites have the highest values. At that, in dry hygrotopes of all types of forest site conditions, the average values of thermoclimate are higher than similar indicators of wetter forest site conditions. The ecotopes of dry fairly fertile sites and fertile sites are characterized by the lowest indicators of the average values of ombroclimate, while fresh and wet fairly infertile pine sites, fairly fertile sites and fertile sites have the highest values. The ecotopes of infertile pine sites and fairly infertile pine sites have the highgest average values of the continentality regime; fairly fertile sites and fertile sites have the lowest values. The ecotopes of infertile pine sites and fairly infertile pine sites have the lowest average values for the cryoclimate, and fairly fertile sites and fertile sites (especially in dry forest site conditions) have the highest values. Conclusions The models of climaphone (thermo-, contrast-, ombro- and cryophones) of forest ecosystems in Forest-Steppe forestry region and climaphones of coniferous, mixed and deciduous forests have been developed for ecological monitoring. Furthermore, the trends of synphytoindication indicators of climatic regimes depending on the change of forest conditions are defined. Comparison of the obtained score in different time periods (for example, once every 5 years) in each region of Ukraine will help assess the intensity, depth, direction (trend), spatial distribution and features of climate regimes due to climate change in Ukrainian forest ecosystems at the regional and national levels which is an important component of forest monitoring under climate change conditions. 4 Figs., 1 Table, 23 Refs. Key words: synphytoindication, forest climatopes, forest monitoring, forest ecosystems, forest conditions, climatic regimes.